Dare to love - Quinn, Tara Taylor (New York Harlequin, 1994)
Too Hot To Handle! When policewoman Andrea Parker was assigned to train six male officers for the DARE program, she certainly didnt expect someone like Doug Avery to be among the trainees. Doug was the kind of guy who instinctively resisted authority, who got his kicks by using other people-especially her-as the butt of his crude jokes. What could he possibly know about being a good example to street kids? Andrea knew she should throw Doug out of the program. But she couldnt make herself do it. Beneath his strutting arrogance, she sensed a hidden vulnerability. Maybe he did know something about hardship, about courage....
Keywords: Fiction